Abundance and Trends of Indo-Pacific Finless Porpoises (Neophocaena phocaenoides) in Hong Kong Waters, 1996–2019 - Jefferson, Thomas A.; Moore, Jeffrey E. (Frontiers in Marine Science, 2020)
The Indo-Pacific finless porpoise (Neophocaena phocaenoides) occurs year-round in waters of southern and eastern Hong Kong. The population biology of the population was studied in the late 1990s and early 2000s, but has not been examined recently. There are several threats facing the animals, and there has been recent concern about this species’ status, due to an increase in the number of strandings in Hong Kong. Line-transect surveys using medium-size vessels have been conducted for small cetaceans in most of Hong Kong’s waters since 1996. We examined the density and abundance of finless porpoises in this area, using a Bayesian hierarchical framework, consisting of a Markov process model used to describe population dynamics and a distance-sampling observation model that links the line-transect data to the latent biological process. Time-series analyses for both dry- and wet-season data from 1996 to 2019 showed annual fluctuations in abundance indices, but no evidence of a significant long-term trend in finless porpoise abundance in Hong Kong. This indicates that the increase in strandings may be related to some factor other than changing population size of Hong Kong finless porpoises. In 2019, there were approximately 176 finless porpoises in Hong Kong’s waters in the dry season (winter/spring), the season of highest use. Highest densities (0.535 porpoises/km2) were recorded in South Lantau in the dry season. Based on the results of the current study, we recommend further survey work, improvements in data collection, possible tagging and molecular work to elucidate population structure, cumulative impact assessment, and the establishment of several marine parks for the conservation of finless porpoises in Hong Kong.